Stimuli-responsive/rheoreversible hydraulic fracturing fluids as a greener alternative to support geothermal and fossil energy production1. Issue 5 (12th May 2015) - Jung, H. B.; Carroll, K. C.; Kabilan, S.; Heldebrant, D. J.; Hoyt, D.; Zhong, L.; Varga, T.; Stephens, S.; Adams, L.; Bonneville, A.; Kuprat, A.; Fernandez, C. A.
<x xml:space="preserve">Abstract</x> A reversible CO2-triggered volume expansion significantly lowers the fracture initiation pressure in highly impermeable igneous rock as compared to conventional fracturing fluids.